APPLICATION OF THE WONG-BAKER FACES PAIN RATING SCALE (WBFPRS) TO MEASURE PAIN LEVELS IN CHILDREN IN THE EAST ASTER WARD OF SARDJITO HOSPITAL, YOGYAKARTA - Fadila Rahmi Ramadhani; Sumarti Endah Purnamaningsih Maria Margaretha; Dwi Prasetyorini (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2025)
Background: Pain is a subjective experience that is difficult to express, especially in children who are not able to express their complaints verbally. Tools such as the Wong–Baker Faces Pain Rating Scale (WBFPRS) can help children communicate pain through facial expressions. Objective: To describe the application of pain assessment using WBFPRS in children in the East Daisy Room of Dr. Sardjito Hospital Yogyakarta. Methods: The study used a descriptive case study design with subjects of 10 children who were hospitalized and experienced pain. Data were obtained through direct observation, semi-structured interviews with parents and medical personnel, and documentation of medical records. The analysis was carried out descriptively. Results: Most children showed moderate pain (60%), severe pain (30%), and severe pain (10%) due to invasive measures such as injection (60%) and IV insertion (10%). WBFPRS makes it easier for nurses to quickly identify pain levels, especially in children who are not able to express complaints verbally. Conclusions: WBFPRS is effective and practical in the assessment of pain in children, as well as improving the accuracy of documentation and nursing interventions. Suggestion: Nurses are advised to use WBFPRS consistently to improve the accuracy of child pain assessments